PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA PT. INDOMARCO ADI PRIMA CABANG MEDAN STOK POINT NIAS KOTA GUNUNGSITOLI - EPILINUS HULU; YUPITER MENDROFA; SOPHIA MOLINDA KAKISINA (JURNAL ILMIAH SIMANTEK, 2022)
In today's increasingly competitive era, every business person wants to win the competition in market competition, this will pay full attention to the strategies he is implementing. Product quality is an important thing that must be considered by entrepreneurs to increase customer satisfaction in order to maintain the market in an era of competition. Even though sometimes the marketing techniques and strategies that are built are mature, they will not run optimally if they do not pay attention to the quality of the products produced. The aims of this study were (1) to find out how much influence the marketing mix has on purchasing decisions at PT. Indomarco Adi Prima Medan Branch, Stok Point Nias, Gunungsitoli City, (2) To find out what factors influence customers in making purchasing decisions at PT. Indomarco Adi Prima, Medan Branch, Stock Point Nias, Gunungsitoli City. The result of this research is that PT. Indomarco Adi Prima Medan Branch Stok Point Nias makes every effort to maintain the quality of the products marketed to the public so that this company continues to exist in the field of product sales. Identify the desires, hopes and needs of the community so that PT. Indomarco Adi Prima Medan Branch Stok Point Nias can find out the types of products provided for storage and then marketed. Thus, no product is delayed too long so that quality is maintained and does not expire.